Study of refrigerant mal-distribution and optimization in distributor for air conditioner. (August 2021) - Pu, Liang; Nian, Luozhu; Zhang, Derun; Gu, Tangtang; Liu, Min; Zhou, Yachen; Yuan, Fengming; Chen, Wei
Abstract: The distribution of two-phase refrigerant has a crucial influence on the efficiency of heat exchanger. Only when the two-phase refrigerant is evenly distributed to each path can the heat exchanger be utilized efficiently. The study aims at exploring the causes of the mal-distribution of refrigerant and designing an optimized structure to mitigate the phase separation and improve the refrigerant distribution. Moreover, the rules of each factor on the distribution are studied. In this paper, Taguchi method is proposed to obtain the importance of each factor on the distribution. The results show that the distance between the elbow and entrance of the distributor, the turning angle and turning radius of the elbow have significant effects on distribution. Finally, the optimized structure of the inlet pipes is proposed. Compared with the traditional structure, the optimized structure has a significant effect on improving the phase separation and the pressure drop is relatively stable. Besides, the optimized structure has low cost and simple production and processing, which provides a new idea for improving refrigerant distribution.